A Methodological Review of Research Syntheses Involving Reading Interventions for Students With Emotional and Behavioral Disorders. (August 2021) - Chitiyo, Argnue; King, Seth A.; Krizon, Margaret D.; Ablakwa, Cephas N.; Markelz, Andrew M.
Students with emotional and behavioral disorders (EBD) exhibit problem behaviors that potentially result in lower performance in reading and related content areas. Researchers and policy makers have increasingly emphasized the need for evidence-based practices (EBPs) in reading. However, conclusions made regarding the effectiveness of the interventions strongly depend on the rigor of systematic reviews and meta-analyses used to identify intervention research. This article applied a set of established quality indicators to literature reviews of reading instruction for children with EBD. Systematic reviews and meta-analyses published in refereed journals between 1996 and 2018 were eligible for inclusion. Identified reviews ( n = 17) generally exhibited a range of methodological strengths; however, authors did not consistently describe coding procedures or assess the quality of primary studies. Implications for the identification of EBP follow a discussion of findings.